Performance of male and female setters and attackers on Olympic-level volleyball teams - Bergeles, N.; Barzouka, K.; Nikolaidou, M. E. (International Journal of Performance Analysis in Sport, 2009)
The purpose of this study was the examination and comparison of performance in attack in relationship with performance in set between Olympic-level volleyball male (M) and female (F) players. A 3-member group of expert coaches assessed the players' actions in set and attack in 16 volleyball games (M=8, F=8) of teams competing in the final phase of the 2004 Olympic Games. Assessment was based on a 5-point rating scale (Eom and Schutz, 1992) and included actions that composed a set of 2 contacts in Complex I (M=1007, F=1248). A cross tabulation statistical procedure with level 4 x 5 calculated performance percentages and frequencies; X2 criterion was used to examine possible differences in the distribution of performance assessment in attack for every performance assessment in set and Z criterion was used to compare percentages of performance assessment between genders. Results showed that the higher the performance of setters, the higher the performance of attackers in both genders. Significantly (P<0.05) lower percentages of male compared to female attackers' average and very good performance were found after receiving good and excellent quality sets, whereas significantly (P<0.05) higher percentages of good performance were shown in favor of male attackers after receiving excellent quality sets.